QUANTITATIVE ASSESSMENT OF MARINE SPONGE CELLS IN VITRO: DEVELOPMENT OF IMPROVED GROWTH MEDIUM - WILLOUGHBY, ROBIN; POMPONI, SHIRLEY A (In vitro cellular & developmental biology. Animal, 2000)
As sources of natural products with potential human therapeutic value, marine sponges are important subjects for cell culture studies. A critical component of any cell culture system is its growth medium. Proceeding from the hypotheses that the thawed, cryopreserved, primary cells would display detectable differential responses and that those responses could be comparatively quantified, this study has established that multiwell screening assays are useful tools for improving medium formulations in cell cultures of the marine sponge, Teichaxinella morchella. Fluorescent probe signals were correlated with known cell densities and viabilities in a 96-well format. Analysis of variance and post-test methods were applied to judge the significance of signal differences seen in a variety of medium formulations. Results from a series of experiments suggested that reducing glutamine and selenium concentrations in the standard medium would result in greater DNA, protein, and esterase activity signals. This was confirmed by the direct comparison of the standard and improved medium formulations. Significantly higher protein content and esterase activity were associated with the improved medium. DNA content was also higher, though not significantly. The result is a new medium formulation that may be more able to support cell growth and division, providing an improved cell culture system for marine sponge cell studies. The assays can be used in additional studies to further improve the in vitro conditions for marine sponge cell culture.